Labour relations for the future: aging management policies to retain older workers - Rodrigues, Ana Raquel Cardoso de Souza; Rodrigues, Ana Cláudia Moreira; Pinto, Ana Maria Gonçalves Lourenço Roque San (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Changes in the European demographic translate urgent revision in human resource management. Indeed, Portugal is getting older, suggesting an aged workforce in the relative near future. To answer this challenge, mechanisms to retain these older workers in the labour market must be adopted. This research aims to understand the influence of human resources management practices suitable for older workers in their decision to remain active in the labour market. In order to achieve this, we conducted an exploratory study, using a questionnaire addressed to the Portuguese population active in the labour market, answered by 434 subjects, age 50 years old or older. Data were analysed using statistical descriptive and frequency analyses, ANOVA’s and simple linear regressions. The results evidenced the adoption of human resources management practices suitable to older workers as promoters of their retention. Significant differences were also identified in the practices that influence the intention to remain active, when compared by sex, sector and company size. The results suggest intervention clues that can promote an improvement in human resource management practices in order to increase the retention of these workers in the labour market. It contributes to the literature by offering an understanding of the (dis)functioning of ageappropriate human resources management practices and of senior workers in the Portuguese labour market. Despite the solidification of human resource management practices as a mechanism to promote the retention of these workers, we suggest future studies that offer systemic approaches to understanding the main factors that promote this retention.